Diagnostic accuracy of the Xpert MTB/RIF assay for tuberculous pericarditis: A protocol of systematic review and meta-analysis. - Guocan Yu; Fangming Zhong; Yanqin Shen; Hong Zheng (PLoS ONE, 2021)
Background Tuberculous pericarditis (TBP) can lead to serious consequences. Early diagnosis and treatment are very important for TBP, but early diagnosis is still very challenging. This study aims to evaluate the diagnostic accuracy of Xpert MTB/RIF for TBP using meta-analysis method. Methods We will search Embase, PubMed, the Cochrane Library, China National Knowledge Infrastructure (CNKI), and the Wanfang database for researches assessing the diagnostic accuracy of Xpert MTB/RIF for TBP until April 2021. Any types of study design with full text will be selected and included. The Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) tool will be used to assess the risk of bias. We will use version 15.0 of the STATA software with the midas command packages to carry out meta-analyses. Results Evidence for diagnostic accuracy of Xpert MTB/RIF for TBP will be provided through the study, and this protocol will be submitted to a peer-reviewed journal for publication. Conclusion This study will provide evidence of Xpert MTB/RIF for TBP.